Beacon of hope : the life of Barack Obama - Rappaport, Doreen (Rappaport, Doreen. Big words series., 2025)
"Before he became the president, Barack Obama was a little boy called Barry. Amid a happy childhood in Hawaii and Indonesia, he also yearned for a better understanding of Black history and culture, and a better sense of his own identity as a Black American. Spurred by conversations around race, injustice, and inequality, he became a community organizer, practiced civil rights law, and was elected to the US Senate. "Yes we can!" became a rallying cry for his message of hope and change throughout the 2008 presidential election--which resulted in Barack Obama becoming the first Black president of the United States. This addition to the highly acclaimed Big Words series celebrates one of the most inspiring American leaders of our time. With evocative illustrations by award-winning artist Tonya Engel, Doreen Rappaport's richly detailed narrative employs rousing quotes from Obama himself and encourages young readers to investigate who they are and who they might one day become." -- Publisher annotation.